THE EFFECTIVENESS OF GLUCOMANNAN AND NANO ACTIVATED-CARBON AS HYPERCHOLESTEROL-LOWERING AGENTS - Gunawan Trisandi Pasaribu; Totok K Waluyo; Gustan Pari; Novitri Hastuti (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2020)
Porang (konjac) plants have long been used as a food source and traditional medicine. Glucomannan derived from porang has been utilised for various uses such as antidiabetic and antihypercholesterolemia agent. This paper studies the mixture of porang flour and nano activated-carbon and its effect on the cholesterol activity of rats. The mixture of porang and activated carbon were subjected to test for male Sprague Dawley rats to test the antihypercholesterolemia activity. The result showed that concerted anticholesterol activity of porang and nano activated-carbon revealed the cholesterol level decreases in rat's blood. However, the different treatments of unleached and leached porang either leached porang and nano activated-carbon applied in the experiments showed that the levels of cholesterol decrease were slightly different (16–18%). Low glucomannan content as the alleged anticholesterol agent was regarded quite effective in lowering the cholesterol level in rat's blood and comparable with those of simvastatin which achieved 18% reduction. Therefore, it indicates potential utilisation as a functional food for a cholesterol-lowering agent. The involvement of activated carbon in the alleged anticholesterol agent (leached porang flour) did little in enhancing the cholesterol level decrease in rat's blood. The glucomannan in both leached porang flour and leached porang flour + nano activated-carbon shows potential utilisation as an anticholesterol agent. Yet, raw (unleached) porang is prospectively potential as a functional food for cholesterol-lowering.